Primary spinal hydatid presenting as Cauda Equina Syndrome: A rare case report - Jain, Pankaj Kumar; Gautam, Sachidanand; Bhat, Pranav Kumar; Seval, Manoj; Magh, Hijilo (Nepal Journal of Neuroscience, 2024)
Primary hydatid of spinal cord is a very rare presentation of relatively common disease. We present the case of 23-year-old female with cauda equina syndrome diagnosed to have a primary spinal hydatid which mimicked Pott’s spine. Initial diagnosis was made with the help of history taking, clinical examination and investigations like MRI and later confirmed with the help of biopsy. High suspicion is required for diagnosis, as it is a rare disease. Complete resection along with Albendazole therapy is the current choice of treatment. Further studies are required for the same as there is a lack of guidelines for management.